2017
DOI: 10.1590/1806-9282.63.04.361
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome prevalence in physiotherapists

Abstract: Physiotherapists in Extremadura present moderate scores for the three dimensions of burnout syndrome, namely, emotional exhaustion, depersonalization and low professional accomplishment. For this reason, they are in the moderate level of the syndrome and very near to the high level, which starts at a score of 66 points. No relation between burnout syndrome and age has been found in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
(10 reference statements)
3
15
3
Order By: Relevance
“…This is reinforced by the significant association between daily working hours, number of patients treated, physical fatigue and global burnout scores. This is in line with previous studies that also found higher burnout in physiotherapists working more than 40 hours per week directly with patients and in those treating more than 20 patients per day (González-Sánchez et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is reinforced by the significant association between daily working hours, number of patients treated, physical fatigue and global burnout scores. This is in line with previous studies that also found higher burnout in physiotherapists working more than 40 hours per week directly with patients and in those treating more than 20 patients per day (González-Sánchez et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, age was weakly associated with emotional exhaustion but not with the global score of burnout. This is partially in line with the literature that often reports no association between burnout and age (González-Sánchez et al, 2017;Pustułka-Piwnik et al, 2014). However, other studies, although not testing directly the association between age and burnout, report that burnout prevalence is higher in physiotherapists aged 46-62 years and lower in physiotherapists aged 21-35 years (Gisbert et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In physiotherapy, personal involvement with patients and family members is high. Moreover, contact is maintained over long periods because of the frequency of interventions in long term or chronic pathologies [16]. Based on scientific results [17], burnout could be higher in physiotherapists than in other health professions.…”
mentioning
confidence: 99%
“…It manifests most commonly in jobs requiring regular interaction with people seeking help, i.e. healthcare workers, including physicians, nurses or physical therapists (González-Sánchez et al 2017;Pradas-Hernández et al 2018;Rotenstein et al 2018). Data from systematic reviews and meta-analyses suggest that burnout may concern up to 80% of healthcare professionals, depending on the type of job, workload, relationships with co-workers, sex (women appear to be more susceptible) and perceived stress (Adriaenssens et al 2015;Kumar 2016;Rabatin et al 2016).…”
Section: Introductionmentioning
confidence: 99%